Perbandingan Tingkat Stres Pembelajaran Terhadap Gangguan Siklus Menstruasi pada Mahasiswa Kebidanan Tingkat Akhir Universitas Airlangga - Adelia Ayu Qurrotul Jannah; Gatut Hardianto; Dewi Setyowati (Al-Hayat: Natural Sciences, Health & Environment Journal, 2025)
The disrupted female reproductive cycle is often related to stress. One of the things that happens to women who experience stress is reproductive disorders related to menstrual events. High stress levels in final semester students are probably due to the large number of assignments that must be completed, high physical activity where final semester female students are in addition to activities on campus such as practicing in hospitals. This irregular menstrual cycle is influenced by several factors, including hormonal changes due to stress in an unstable emotional state. This study aims to analyze the comparison of stress levels on menstrual cycle disorders of midwifery final level students at Airlangga University. This study uses an observational analytic design with a cross-sectional approach. The instrument used is a questionnaire distributed via online g-form. The research data were analyzed using the Mann-Whitney U test. The results showed that the most respondents experienced no stress as much as 53 or 71.6%, while those who experienced stress were 21 or 28.4%.. it can be concluded that there is a significant difference in the level of stress with disruption of the menstrual cycle in final level students of midwifery at Airlangga University